Changes in the structure of melolonthidae (coleoptera: scarabaeoidea) assemblages along a temporal gradient in a natural reserve in Chaco, Argentina - Ibarra Polesel, Mario Gabriel (2017)
Fil: Ibarra Polesel, Mari Gabriel. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.